2004
DOI: 10.1080/09637480400002800
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and sensory quality of stirred soursop (Annona muricataL.) yoghurt

Abstract: Soursops (Annona muricata L.) are highly aromatic fruits with white juicy flesh and are native to tropical North and South America. The ripe fruits are highly perishable, as they become soft and easily bruised. The objectives of the study were to incorporate soursop nectar at 0%, 5%, 10% and 15% in stirred yoghurts and to analyse the products for chemical and sensory quality. A focus group evaluated the initial yoghurts for process modifications. Yoghurts were evaluated on sensory attributes of appearance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
3
19
1
1
Order By: Relevance
“…Pumpkin contains a yellow color from carotenoids contributes to yogurt color which may not favored for panelists. Improving the flavor and color of yoghurt fortified with fruits and vegetables were confirmed [5] [16] [27]. Mouth feel of pumpkin-yoghurt were slightly improved as pumpkin was added when compared to CY.…”
Section: Organoleptical Parameters Of Different Prepared Stirredmentioning
confidence: 84%
See 1 more Smart Citation
“…Pumpkin contains a yellow color from carotenoids contributes to yogurt color which may not favored for panelists. Improving the flavor and color of yoghurt fortified with fruits and vegetables were confirmed [5] [16] [27]. Mouth feel of pumpkin-yoghurt were slightly improved as pumpkin was added when compared to CY.…”
Section: Organoleptical Parameters Of Different Prepared Stirredmentioning
confidence: 84%
“…Yoghurts may also be fortified with bioactive rich-extract like: caffeine, guarana, green tea extract, coenzyme Q10, ginseng, aloe vera, cranberry, fiber, and olive vegetable water [3] [4]. Lutchmedial et al [5] found that most panelists preferred yoghurt with 10% and 15% soursop fruits and confirmed that provided high percentage daily values of zinc, phosphorus, calcium, and much of protein. Fayed [6] investigated ingredients namely, isoflavones and γ-Aminobutyric acid, with emphasis on their fitness for fortification of yoghurt to be consumed as a functional food.…”
Section: Introductionmentioning
confidence: 99%
“…Lutchmedial et al . () conducted focus groups to ascertain early consumer reaction to prototype blends of soursop fruit yogurt at varying levels of added fruits. The information gained from these focus groups lead to a modification of the original fermentation process, and incubation times in order to produce a product that was consumer friendly before continuing on to chemical analysis.…”
Section: Qualitative Approachesmentioning
confidence: 99%
“…Lutchmedial et al (2004) avaliaram atributos sensoriais de aparência e cor, corpo e sabor, textura e aroma, e qualidade geral em iogurtes incorporados de néctar graviola (0%, 5%, 10% e 15%). Os resultados revelaram que os iogurtes com 10% e 15% de néctar de graviola tiveram o maior índice de qualidade global (p<0,05), mas diferiram em sabor e aroma de iogurte natural em relação ao iogurte com 5% de néctar de graviola (p<0,05).…”
Section: As Bactérias Probióticas Lactobacillus Acidophilus E Bifi Dounclassified